A Space for Sound - Mills, Liz (Recherches sémiotiques / Semiotic Inquiry, 2016)
The focus of this article is Western theatre voice practice and discourse. With the voice conceived as the trace of language, the main intention is to reveal interstices for creative vocal or sonorous play by unsettling the relationship between voice and language.The project references the shift to the ‘natural voice’ in Western theatre voice practice and how, in spite of this shift to sound that is strongly located in the person of the performer, voice does not exploit the riches of either its originating practice in orality or its own essential nature as sonorous vocality. This article proposes that Western theatre voice’s strong link to a devocalized logos as argued by Cavarero, and logos as text informed by Habermas’s concept of communicative rationality, do not allow the voice to transcend a single representation rooted in language.